A comprehensive study of Titan's magnetic pile-up region during the Cassini era. (15th October 2020) - Chen, Chen; Simon, Sven
Abstract: While Saturn's largest moon Titan is devoid of an intrinsic magnetic field, draping of the giant planet's magnetospheric field around Titan's ionosphere generates a pile-up region at the moon's ramside. In this study, we analyze Cassini magnetic field data from all 126 Titan flybys to systematically characterize the extensions and magnitudes of the field enhancements at its ramside. Along each flyby trajectory, the segments where Cassini crossed the piled-up magnetic field are determined, and altitude profiles of the pile-up strength are also generated. We investigate the dependency of the extension and strength of the pile-up region on various parameters, such as the Saturn local time and the magnetospheric environment to which Titan is exposed. In this way, we generate a comprehensive picture of Titan's ramside magnetic pile-up region during the Cassini era. Our major findings are: (1) The extensions of the observed pile-up reveal an asymmetry between the Saturn-facing and Saturn-averted sides caused by the large gyro-radii of ionospheric pick-up ions. (2) The observed pile-up radial extensions are nearly independent of Titan's orbital position. (3) The lower boundary of the pile-up region is located at an altitude of 0.35 Titan radius, denoting the average altitude of the magnetic ionopause. (4) Considering the error bars, the altitude profiles of the pile-up strength show a stable picture, i.e., the radial profile of the field magnitude is independent of Saturn's magnetospheric environment and local time. Highlights: Extensions of the observed pile-up reveal an asymmetry between the Saturn-facing and Saturn-averted sides. Observed pile-up radial extensions are nearly independent of Titan's orbital position. Lower boundary of the pile-up region is located at an altitude of 0.35 Titan radii. Altitude profiles of the pile-up strength are independent of Saturn's magnetospheric environment and local time.